Echinocephalus inserratus sp. n. (Nematoda: Gnathostomatidae) from the stingray Pastinachus ater (Dasyatidae) and new records of congeneric and some other nematode larvae from teleost fishes off New Caledonia - Moravec, Frantisek; Justine, Jean-Lou (Folia parasitologica, 2021)
Based on light and electron microscopical studies, a new nematode parasite, Echinocephalus inserratus sp. n. (Spirurida: Gnathostomatidae), is described from the spiral valve of the broad cowtail stingray Pastinachus ater (Macleay) (Dasyatidae, Myliobatiformes) from off New Caledonia. The new species is morphologically and biometrically most similar to Echinocephalus overstreeti Deardorff et Ko, 1983, differing from it mainly in the absence of serrations on the posterior parts of pseudolabia and on interlabia, and in having a longer gubernaculum (150-299 µm long). Morphologically unidentifiable, mostly encapsulated larvae of Echinocephalus spp. were recorded from the following six species of teleost fishes collected in New Caledonian waters, serving as paratenic hosts: Perciformes: Acanthopagrus berda (Forsskål) (Sparidae) and Nemipterus furcosus (Valenciennes) (Nemipteridae); Tetraodontiformes: Abalistes stellatus (Anonymous), Pseudobalistes fuscus (Bloch et Schneider) (both Balistidae), Lagocephalus sceleratus (Gmelin) (Tetraodontidae) and Aluterus monoceros (Linnaeus) (Monacanthidae). Co-parasitising larvae of Ascarophis sp. and Hysterothylacium sp. were also collected from P. fuscus. All these findings represent new host and geographical records. A key to valid species of Echinocephalus Molin, 1858 is provided.
Keywords: Parasitic nematode; New Caledonia; nemoci ryb; Fish Diseases; Gnathostomatoidea; prevalence; Thelazioidea; larva; Nová Kaledonie; Female; Host-Parasite Interactions; Microscopy, Electron, Scanning; zvířata; rejnokovití; infekce hlísticemi řádu Spirurida; paratenic host; ženské pohlaví; Male; Skates, Fish; mikroskopie elektronová rastrovací; marine fish; South Pacific.; elasmobranchs; Larva; Prevalence; Animals; mužské pohlaví; interakce hostitele a parazita; Spirurida Infections